2017
DOI: 10.1371/journal.pone.0175716
|View full text |Cite
|
Sign up to set email alerts
|

Talent identification and recruitment in youth soccer: Recruiter’s perceptions of the key attributes for player recruitment

Abstract: Using the modified Delphi method, we aimed to understand the attributes youth coaches and recruiters perceive as important when identifying skilled youth performance at the entry level of representative soccer in Australia (i.e., Under 13 years). Furthermore, we also aimed to describe the current methods youth coaches and recruiters use to assess and identify these attributes in youth players. Australian regional youth technical directors and coaches (n = 20) completed a three stage process, including an initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
138
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(185 citation statements)
references
References 37 publications
17
138
2
3
Order By: Relevance
“…The findings from this study highlight that somatic maturity, anthropometric and physical performance characteristics exert an influence on the decision-making process regarding player retention within this elite academy. This contradicts data obtained from Australia in which youth coaches and recruitment staff indicated that technical, tactical and psychological attributes are the most important factors in terms of talent identification 64 . On the other hand, our findings appear to align with research establishing that organisational pressures and physical maturity exert an influence on the selection process adopted by the coaches of 12 to 15-year-old football players 65 .…”
Section: Discussioncontrasting
confidence: 88%
“…The findings from this study highlight that somatic maturity, anthropometric and physical performance characteristics exert an influence on the decision-making process regarding player retention within this elite academy. This contradicts data obtained from Australia in which youth coaches and recruitment staff indicated that technical, tactical and psychological attributes are the most important factors in terms of talent identification 64 . On the other hand, our findings appear to align with research establishing that organisational pressures and physical maturity exert an influence on the selection process adopted by the coaches of 12 to 15-year-old football players 65 .…”
Section: Discussioncontrasting
confidence: 88%
“…TI has received significant research attention over the last decade. Yet, coach subjective influence continues to play a substantial role during TI processes (Larkin & O'Connor, 2017). Given advancements in technology and resources more readily available to coaches and practitioners, it was assumed that our ability to identify and predict talent would also progress.…”
Section: Limitations Of Talent Identificationmentioning
confidence: 99%
“…Practitioners have attempted to identify key components associated with improved soccer performances. However, it remains unclear how these variables influence competitive match play, or coach perception and rating (Güllich, 2014;Larkin & O'Connor, 2017;Unnithan et al, 2012). Inevitably, despite attempts by researchers and practitioners to improve accuracy and appropriateness of TI processes, these processes must align with a demonstrable difference in performance, or positively inform the coach or decision-makers responsible during selection/deselection processes.…”
Section: Challenges Of Talent Identificationmentioning
confidence: 99%
“…Due to the multifaceted nature of talent some have called for more objective predictors of future 75 potential (i.e. Larkin & O'Connor, 2017) or research designs that are in a position to infiltrate 76 applied talent identification practice (Collins, MacNamara, & Cruickshank, 2018). 77…”
Section: Introduction 31mentioning
confidence: 99%